Sala de aula invertida para o letramento digital de alunos de graduação em Direito - Araujo, Karyne Machado de (2023)
We are living at the beginning of the 21st century, also known as the milestone of the Technological Revolution, compared by many to the Industrial Revolution, given the importance of the transformations brought about by information and communication technologies, at national and global levels. Consequently, the science of Law and legal praxis are undergoing a profound evolution, a portrait of the relevant changes in life in society, arising from the massive dissemination of the use of various technological artifacts. In 2018 and 2021, through resolutions 5/2018 and 2/2021 of the Ministry of Education, the National Curricular Guidelines for higher education courses in Law were modified. Digital literacy and training in Digital Law were included. The teaching-learning of digital literacy has a strong technological appeal. Therefore, the use of active teaching methodologies, among which the flipped classroom stands out, presents itself as an appropriate strategy for transmitting this new knowledge. The present study was based on the process of creating flipped classes for higher education, defined by Robert Talbert in the work entitled “Guide for the Use of Flipped Learning in Higher Education”, and presented a proposal for the construction and application of classes for digital literacy of Law academics through the use of the flipped classroom. The inquiry was constructed through qualitative, exploratory and field research. It included studies on digital literacy, active methodologies, Advocacy 4.0 and Justice 4.0; research on the technological topics covered in the experiment; creation of classes and production of video classes; and carrying out the course “Digital Literacy for Law Students”, taught to students of the Environmental Law discipline of the Bachelor's degree in Law, at the Faculty of Law of the Federal University of Ceará (UFC). The results obtained with the validation of the process used showed that the use of the flipped classroom for the digital literacy of Law academics can reduce the technological knowledge deficit of future lawyers and better prepare them for today's job market. Furthermore, the work resulted in the design of a teaching guide entitled “A Guide for Using the Flipped Classroom in Digital Literacy for Undergraduate Law Students”, to assist teachers in the preparation and implementation of classes.